DYSPHAGIC COMPLAINT EVALUATION ON PATIENTS ON OTORRINOLARYNGOLOGY AMBULATORY AT ONOFRE LOPES UNIVERSITY HOSPITAL - Ferreira, Lidiane Maria de Brito Macedo; Bezerra, Daniel de Menezes Cortês; Fernandes Moreira, Victor Bruno; Magalhães Júnior, Hipólito Virgílio; Godoy, Cynthia Meira de Almeida (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Purpose: The present study aims to to evaluate, diagnose, treat and refer patients with swallowing disorders, in different age groups, referred to the otorhinolaryngology outpatient clinic of Onofre Lopes University Hospital. Methods: The consultations took place on a frequency of once a week for a period of 12 months. They consisted of speech therapy evaluation, nutritional risk and otorhinolaryngology evaluation, in addition to the Fiberoptic endoscopic evaluation of swallowing. Results: The average age of the patients seen was 62.5 years, and the main comorbidities presented were neurological. Most patients were classified as having mild dysphagia and indicated oral diet with multiple consistencies, but with the need for special preparation or compensation. Approximately 25% of patients with dysphagic complaints had a risk of malnutrition, a risk that was statistically more significant in those with severe dysphagia (37.5%) related to those with mild/moderate dysphagia. Among the parameters observed in the fiberoptic endoscopic evaluation of swallowing, the presence of salivary stasis, aspiration and penetration were those that showed a statistical association with nutritional risk. Conclusion: The work concludes that nutritional assessment should play a prominent role in the routine of outpatient clinics specialized in dysphagia, reducing the risk of adverse events and improving the general health and quality of life of patients with these complaints.